LINGUISTIC BOUNDARIES AND POLITICAL BOUNDARIES: LINGUISTIC AND SOCIO-HISTORICAL RELATIONS AT THE BORDER BETWEEN BRAZIL AND FRENCH GUIANA - Kelly Cristina Nascimento Day (Cadernos de Letras da UFF, 2013)
This article highlights the reality of the Franco-Brazilian boundaries, permeated by its historical and social aspects, and the study of the contact. Starting from the concept of contact and from the phenomena that it makes emerge, we have constructed a historical, socio-cultural and linguistic framework of the Brazilian border with French Guiana and of the results of such contact on the inhabitants daily life. Finally, we discuss issues concerning educational language policies in vogue at the region.